The Effect of Earnings Management on the Relationship between Corporate Governance and Stock Liquidity: An Empirical Study in IDX - RETNO YUNI NUR SUSILOWATI (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to examine whether corporate governance practices influence firms' stock liquidity, and if they do, whether such relationship is mediated by earnings management practices. Corporate governance practices will be able to influence the level of stock liquidity effectively only if corporate governance practices can curb the practices of earnings management. The data were obtained from non-financial companies listed in the Indonesia Stock Exchange (IDX) that participated in the CGPI (Corporate Governance Perception Index) surveys by IICG (Indonesian Institute for Corporate Governance) in 2003-2007. Three steps regression analysis are employed as suggested by Baron and Kenny (1986). The results indicate that corporate governance has a positive effect on stock liquidity and that relationship is partially mediated by earnings management. Further analysis reveals that, the greater the earnings management practices, the higher the stock liquidity. This matter generates notion that investors do not realize the existence of earnings management practices conducted by companies.